Rural‐Urban Differences in Prostate‐Specific Antigen (PSA) Screening and Its Outcomes in New Zealand. Issue 1 (14th July 2015) - Obertová, Zuzana; Hodgson, Fraser; Scott‐Jones, Joseph; Brown, Charis; Lawrenson, Ross
Abstract: Purpose: To examine prostate‐specific antigen (PSA) screening patterns and outcomes in rural and urban men in New Zealand. Methods: Men aged 40+ years were identified from 18 rural and 13 urban general practices across the Midland Cancer Network region. Computerized practice records were cross‐referenced with community laboratory data to ascertain the number and level of PSA tests undertaken in 2010 and 3 years prior. For men with an elevated PSA result in 2010, practice records were searched for information on specialist visits, and they were cross‐referenced with histology reports regarding biopsy and prostate cancer diagnosis. Findings: The study population included 34, 960 men aged 40+ years, of whom 48% were enrolled in rural practices. Men in rural practices were 43% less likely to be screened with a PSA test in 2010, but they were 53% more likely to have an elevated PSA result. The prostate cancer detection rate from all screened men was 6 per 1, 000 for rural men compared with 3 per 1, 000 for urban men. Rural men were more likely diagnosed with Gleason score 9 tumors and metastatic disease. Conclusion: Significant differences were found in PSA screening patterns between rural and urban general practices. Due to lower screening rates, rural men were more likely to be diagnosed with prostate cancer when screened and also seemed to be diagnosed with more advanced disease compared with urban men. Despite ongoing discussions about the benefits and harms of PSA screening, PSA testing as such seems to be under‐utilized in New Zealand rural practices.